ANALISIS PENGUASAAN KATA â€œBIJINGâ€, â€œJIUJINGâ€ DAN â€œDAODIâ€ PADA MAHASISWA ANGKATAN 2015 PRODI MANDARIN UNTAN - Ningsih, Juliyanty; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstractâ€œDaodiâ€, â€œjiujingâ€ and â€œbijingâ€ are three modality adverbs which have relevant meaning. In some conditions, these three words are exchangeable, but in some other conditions they arenâ€™t. And for some cases, only between two words are exchangeable, and the other one word is left unexchangeable. Because of their complicated relations, students tend to make mistakes while using these three words. To understand how well the students of Mandarin education study program at Tanjungpura University Teacher Training and Education Faculty Year 2015 master the modality adverbs â€œdaodiâ€, â€œjiujingâ€ and â€œbijingâ€ and to find out the difficulties they have faced while studying these three modality adverbs, the writer has done a test towards the students by using literature study method and evaluation method. The result of the research shows that the students have been able to differentiate the meaning of these three words and have mastered their sentence structure. However, there are some functions of the words which have not being mastered pretty well by the students.keywords : DaodiÂ Â Â Â Â Â Â Â  JiujingÂ Â Â Â Â Â Â Â Â Â Â  BijingÂ Â Â Â Â Â Â Â  Mastery Condition